2009
DOI: 10.1007/s11103-009-9464-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis during somatic embryogenesis of the tropical monocot Elaeis guineensis: evidence for conserved gene functions in early development

Abstract: With the aim of understanding the molecular mechanisms underlying somatic embryogenesis (SE) in oil palm, we examined transcriptome changes that occur when embryogenic suspension cells are initiated to develop somatic embryos. Two reciprocal suppression subtractive hybridization (SSH) libraries were constructed from oil palm embryogenic cell suspensions: one in which embryo development was blocked by the presence of the synthetic auxin analogue 2,4-dichlorophenoxyacetic acid (2,4-D: ) in the medium (proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 64 publications
1
40
0
7
Order By: Relevance
“…The presence of ESTs homologous to TRANSPO-SASE was exclusively associated with the occurrence of embryogenesis in E. guineensis [19] but transposons were detected in tissues of tenera collected in and ex vitro with no remarkable differences in distribution/localization [44].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The presence of ESTs homologous to TRANSPO-SASE was exclusively associated with the occurrence of embryogenesis in E. guineensis [19] but transposons were detected in tissues of tenera collected in and ex vitro with no remarkable differences in distribution/localization [44].…”
Section: Discussionmentioning
confidence: 91%
“…However, the expression rates of these two last genes diverged among callus lines with different genotypes and it was concluded that transcription had been modulated principally by stress [18]. At last, a TRANS-POSASE was among the ESTs expressed exclusively in actively proliferating E. guineensis embryogenic cell cultures and was not expressed in nonmultiplying cultures [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, specific allocation of certain GO categories into a particular library might have a relationship with the function of that particular tissue at that time. For example oxygen binding sub category, which is represented only in 9ME has been previously reported in the oil palm initiation library but not in the proliferation library (Lin et al, 2009), suggesting the GO terms associated with early stages of embryogenesis. When the biological process ontology is considered, cellular process and metabolic process were the main subcategories bearing higher number of GO terms in all four libraries.…”
Section: December 2015mentioning
confidence: 84%
“…A total of 19,471 embryogenesis related ESTs were obtained from Low et al (2008) and Lin et al (2009). The ESTs libraries were assembled using CAP3 program resulting to 13,020 sequences of contigs and singletons (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Target genes were derived from Expressed Sequence Tags (ESTs) from Low et al (2008), and Lin et al (2009) which were deposited in GenBank database EY396120-EY413718 and GH635901-GH637767. ESTs were subsequently assembled using CAP3 program (Huang & Madan 1999).…”
Section: In Silico Selection Of Snps Markermentioning
confidence: 99%